Assessment of Burden Among Family Caregivers of Schizophrenia: Psychometric Testing for Short-Form Zarit Burden Interviews - Yu, Yu; Liu, Zi-wei; Zhou, Wei; Chen, Xiao-chuan; Zhang, Xing-yu; Hu, Mi; Xiao, Shui-yuan (Frontiers in Psychology, 2018)
Objective: Although various short forms of Zarit Burden Interview (ZBI) have been developed, there is a lack of standard psychometric testing and comparison among them. The study aims to examine the psychometric properties of nine short versions of the most frequently used ZBI among a sample of schizophrenia caregivers and to find the one with the best performance. Methods: Cross-sectional door-to-door survey ZBI-22 and a series of validated instrument data from 327 family caregivers of schizophrenia patients in a Chinese rural community were conducted from October 2015 to January 2016. Reliability was assessed using Cronbach’s alpha. Validity including construct validity, known group’s validity and criterion validity were assessed by Spearman correlations and Mann-Whitney U tests. Overall discrimination ability was evaluated using the area under the receiver operating characteristic curve (AUC). Results: Reliability was acceptable for the Gort ZBI-4 (α=0.58) and good for the other forms (α= 0.70 to 0.84). Construct validity were good across all various ZBI forms (r=-0.34 to 0.65), with the Gort ZBI-7 showing the highest correlations. Known groups’ validity showed inconsistent results among various short forms, with the Higginson ZBI-1 and the Gort ZBI-7 displaying the best performance. Criterion validity was generally good for all short forms, with the Gort ZBI-7 showing the highest correlation. Discriminative ability was also good for all short forms (AUC range: 0.849 to 0.982), with various cutpoints proposed. Conclusions: This study provides support for the reliability, validity, and discriminative ability of the nine various short forms of ZBI for use among schizophrenia family caregivers, with the Gort ZBI-7 endorsed as the best one.